The Winter of Our Discontent Movie Still - Hallmark Hall of Fame Productions; Lorimar Productions:::Creator::::::::::::
Donald Sutherland (Ethan Hawley) stands with Tuesday Weld (Margie Young-Hunt) on his right and Teri Garr (Mary Hawley) on his left.